Analysis of Factors Caused Out of School in Kupang Timur District, Kupang Regency, Nusa Tenggara Timur Province - Nitanel Elia, Yandri; Liliweri, Aloysius; Melkisedek Noh Bernabas Cervesius Neolaka (Devotion : Journal of Research and Community Service, 2022)
The problem of children dropping out of school and children's participation in school are like two sides of a coin that are difficult to separate because they both talk about the future of children as the nation's golden generation. From the available data, the School Participation Rate (APS) is distinguished by age group: 7-12 years (SD/Equivalent: 98.45%), 13-15 years (SMP/Equivalent: 95.25%), and 16-18 years (high school/equivalent: 74,92%). This means that with increasing age, school participation also decreases. Looking at school statistics in Kupang Regency, it should be able to reach all children in continuing education at every level. However, the reality is the opposite. The participation rate for each level continues to decline from time to time, more tragically, the dropout rate is also increasing. This study aims to analyze the factors causing school dropouts in the East Kupang sub-district, Kupang district, East Nusa Tenggara province. This study uses a descriptive research method with a qualitative approach which was carried out in Kupang Kupang Regency because of the 24 sub-districts in Kupang Regency, the informants used purposive techniques with the number of informants as many as 50 people. Based on the results of research conducted by the author, it is known that the factors that cause children to drop out of school in SMA Negeri Kupang Timur District, Kupang Regency, Nusa Tenggara Province in 2018, 2019, 2020, and 2021 consist of internal factors. factor. namely promiscuity and low interest in children to school while external factors are economic factors, lack of parental attention, culture and history as well as the location or location of the school.